Penerapan QRCode Untuk Presensi Mata Kuliah Mahasiswa Dengan Yii Framework - Kristian Suryajaya The; Djoni Haryadi Setiabudi; Justinus Andjarwirawan (Jurnal Infra, 2020)
In this Presence activity it is still done manually and still uses paper for the Presence system, and there are still many cheats in the Presence process. There are several studies that have used the Yii Framework for the Presence system but in that study it was still less successful in overcoming the problem well and the lack of features that prevented fraud in the presence. This research was made by conducting a literature study on previous research studies aimed at learning in the framework and learning about the presence system, then an analysis of the old system, problem analysis and needs analysis will be made and a website for the presence system with QRCode using the framework yii , and the system will be tested whether the system is suitable for use. The results obtained from this application are students can attend online using QRCode and check according to the location of the student and the time at the time of attendance.